On batholiths and volcanoes: intrusion and eruption of late Cenozoic magmas in the Glacier Peak area, North Cascades, Washington - Tabor, R. W. (Rowland W.); Crowder, D. F. (Dwight Farnsworth), 1929- (Geological Survey professional paper, 1969)
Description of the Cloudy Pass batholith, the overlying Gamma Ridge volcanic rocks, and the still younger Glacier Peak volcano with discussion of the source magmas, their genetic ties, and the structures controlling their emplacement and eruption.